1994
DOI: 10.1243/pime_proc_1994_208_379_02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extreme Pressure (EP) Lubricants on the Life of Rolling Element Bearings

Abstract: Bearing tests showed that lubricants containing sulphur and phosphorus extreme pressure (EP) additives reduce the life of rolling bearings compared with similar lubricants without EP additives. High-resolution electron microscopy revealed a remarkable difference of contact surface topography and microstructural changes between bearings tested with or without EP additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The results from the ThCRB and DGBB tests performed in this study with oil A/A1 point out that certain oil formulations can have an effect on bearing performance under certain conditions. 13,14 In this case, also leading to the formation of WECs and the associated bearing failure. For the first time, this study shows that the described effect seems to affect bearings with different geometry, both axial and radial bearing types in a reproducible way.…”
Section: Influence Of Oil Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the ThCRB and DGBB tests performed in this study with oil A/A1 point out that certain oil formulations can have an effect on bearing performance under certain conditions. 13,14 In this case, also leading to the formation of WECs and the associated bearing failure. For the first time, this study shows that the described effect seems to affect bearings with different geometry, both axial and radial bearing types in a reproducible way.…”
Section: Influence Of Oil Compositionmentioning
confidence: 99%
“…It is known that certain oil-additive systems reduce the bearing life, 13,14 although the precise mechanism on how this happens is not very clear. It is assumed that some sort of weakening effect occurs in the bearing material so that cracks initiate even under relatively low stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of additives found in lubricants have been shown to promote WSF occurrence, these include; extreme pressure (EP) and anti-wear (AW) additives consisting of sulphur and phosphorus compounds [66,67], where sulphur aids in hydrogen diffusion by preventing atomic hydrogen recombination [68] and formulations of AW zinc dithiophosphates (ZDDP/ZnDTP/ZnDDP) with detergent/rust preventative calcium sulphonate additives [6,61,[69][70][71][72][73][74].…”
Section: Influence Of Oilmentioning
confidence: 99%
“…In greaselubricated bearings, additives can be locally consumed on the raceways and are hardly replaced. Wan et al [10] have shown that some EP additives can in some cases promote material fatigue and therefore should be used with care in lubricants for rolling element bearings. Many commonly used additives are currently being phased out because of environmental, health and safety aspects.…”
Section: Prevention Of Bearing Surface Damage By Tribological Coatingsmentioning
confidence: 99%